2016
DOI: 10.1037/trm0000063
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between trauma centrality and posttraumatic stress disorder symptoms: A moderated mediation approach.

Abstract: Background and Objectives The degree to which a traumatic event is seen as central to one's sense of self (trauma centrality) has been associated with posttraumatic stress disorder (PTSD) symptoms. Based on cognitive models of PTSD that highlight the role that maladaptive appraisals play in generating PTSD symptoms, we hypothesized that appraising a trauma as violating one's core beliefs and goals mediates the link between trauma centrality and PTSD symptoms. Further, we reasoned that coping ability moderates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…The final regression, however, indicated that only catastrophizing mediated the relationship between event centrality and strength of maladaptive appraisals. These findings are in line with previous research indicating that individual differences in coping mediate the relationship between event centrality and maladaptive trauma appraisals (George, Park, & Chaudoir, 2016).…”
Section: Summary Of Secondary Measuressupporting
confidence: 92%
“…The final regression, however, indicated that only catastrophizing mediated the relationship between event centrality and strength of maladaptive appraisals. These findings are in line with previous research indicating that individual differences in coping mediate the relationship between event centrality and maladaptive trauma appraisals (George, Park, & Chaudoir, 2016).…”
Section: Summary Of Secondary Measuressupporting
confidence: 92%
“…Lancaster et al (2011) showed that no significant difference could be found between their two proposed mediation models, which could suggest that event centrality is a type of posttraumatic appraisal. Further studies showed that the effect of event centrality was partially mediated by the violation of beliefs and intrinsic goals (George et al 2016), or by self-efficacy (Chung et al 2017). The mediation model in a bereaved sample tested by Boelen (2012b) showed that the relation between event centrality and PTSD symptoms was fully mediated by memory intrusiveness, negative appraisals, rumination, and depressive avoidance.…”
Section: Introductionmentioning
confidence: 98%
“…However, frequent exposure to patient trauma and mortality may elicit symptoms of posttraumatic stress disorder (PTSD) . PTSD is conceptualized to arise in response to life‐threatening events that threaten core beliefs and expectations, including through the repeated witnessing or hearing of others' trauma as part of one's professional role . Review of epidemiological studies suggests that PTSD affects less than 7% of the population over the lifetime .…”
Section: Introductionmentioning
confidence: 99%
“…1 PTSD is conceptualized to arise in response to life-threatening events that threaten core beliefs and expectations, including through the repeated witnessing or hearing of others' trauma as part of one's professional role. [2][3][4] Review of epidemiological studies suggests that PTSD affects less than 7% of the population over the lifetime. 4 In pediatric oncology, repeated exposure to patient trauma and mortality may threaten core beliefs such as the commonly held belief that it is "unnatural" for children to die and trigger symptoms of re-experiencing, hyperarousal, negative mood.…”
Section: Introductionmentioning
confidence: 99%